Management of Obstetric Emergencies at the Maternity Center of the University Hospital Center of Oueme-Plateau (CHUDOP) in Benin - TONATO EPSE BAGNAN, JOSIANE ANGÉLINA ADJOUA; LOKOSSOU, Mègnissè Sèna H. S.; OGOUDJOBI, OGOURINDÉ MATHIEU; TOGNIFODE, Véronique; OBOSSOU, Achille; PERRIN, RENÉ-XAVIER (My University, 2017)
Introduction: Obstetric emergencies constitute public health problems in our countries. Objective: To analyze how obstetric emergencies are managed from the clinical, therapeutic, and prognosis point of view in the gynecology and obstetrics department of the Centre Hospitalier Universitaire Départemental of Ouémé-Plateau. Patients and Methods: It was a cross-sectional, descriptive and analytical study carried out at the maternity CHUD-OP over a period of 06 months from February 2016 to August 2016. It was conducted on an exhaustive sample of all patients admitted to the CHUD-OP maternity and treated for complications of gravido-puerperium. Nonobstetric emergencies were not included. Statistical analysis and testing were performed on CS PRO 6.2 and SPSS software by comparing averages and deviations, using the Pearson chi-square for the dichotomous variables, accepting a significant probability p ≤ 0.05. The principles of confidentiality were respected. Results: The frequency of admission of obstetric emergencies was 34.9%. Epidemiologically, the mean age was 27.35 ± 5.71 years. 31.4% were nulliparous, and 69.3% had low-paid occupational activities. Clinically, the reference was in 70.4% of cases the mode of admission, non-medical (95.1%) and without venous access (59.1%). The causes were: dystocia (30.7%); hemorrhagic emergencies (25.9%); hypertensive emergencies (21.5%); fetal hypoxia (17.8%) and infections (4.0%). Therapeutically, the average duration of a treatment was 4.1 ± 1.3 hours and was performed in 67.5% of cases by a caesarean. At the prognostic level, the sequences of layers were complicated in 10.1% of the cases, marked mainly by anemia (38.1%) and arterial hypertension (28.6%). Maternal and neonatal lethality cases represented 3.8% and 11.5%, respectively. Conclusion: The maternal and fetal mortality rate associated with obstetric emergencies is still high at CHUDOP. The reductionof morbidity and mortality requires the improvement of the quality of care and the reference system.
Keywords: Obstetric emergency; Morbidity; Mortality